2009
DOI: 10.15288/jsads.2009.s16.12
|View full text |Cite
|
Sign up to set email alerts
|

Magnitude of and Trends in Alcohol-Related Mortality and Morbidity Among U.S. College Students Ages 18-24, 1998-2005

Abstract: ABSTRACT. Objective: The aim of this study was to estimate, among college students ages 18-24, the numbers of alcohol-related unintentional injury deaths and other problems over the period from 1998 through 2005. Method: The analysis integrated data on 18-to 24-year-olds and college students from each of the following data sources: the National Highway Traffi c Safety Administration Fatality Analysis Reporting System, Centers for Disease Control and Prevention Injury Mortality Data, National Coroner Studies, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
612
2
7

Year Published

2012
2012
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 986 publications
(625 citation statements)
references
References 10 publications
4
612
2
7
Order By: Relevance
“…Such heavy drinking takes a considerable toll: an estimated 1,800 deaths, 97,000 sexual assaults, and 599,000 injuries are attributable to alcohol use among college students on a yearly basis (Hingson et al, 2005(Hingson et al, , 2009. Alcohol is also associated with 66% of college suicides (the third leading cause of death for young adults; Barrios et al, 2000).…”
mentioning
confidence: 99%
“…Such heavy drinking takes a considerable toll: an estimated 1,800 deaths, 97,000 sexual assaults, and 599,000 injuries are attributable to alcohol use among college students on a yearly basis (Hingson et al, 2005(Hingson et al, , 2009. Alcohol is also associated with 66% of college suicides (the third leading cause of death for young adults; Barrios et al, 2000).…”
mentioning
confidence: 99%
“…H EAVY DRINKING (e.g., consuming four or more standard drinks on an occasion) is seen in almost half of college students, and alcohol use disorders are observed in about 20% of 18-to 29-year-olds (Hingson et al, 2009;Johnston et al, 2015;Kessler et al, 2005). Such heavy drinking contributed to injuries in more than 10% of college students and overall shortens life spans by about 10% in the general population (Hingson et al, 2009;Lundin et al, 2015).…”
mentioning
confidence: 99%
“…For example, brief motivational interventions have shown efficacy in reducing overall drinking and related consequences in some studies (e.g., Marlatt et al, 1998;Murphy et al, 2004;White et al, 2007), but other studies have observed reductions in drinking but not consequences (e.g., Carey et al, 2010;Larimer et al, 2001;Turrisi et al, 2009). Overall, although significant advances have been made to combat risky drinking and problems during the first year of college, the consensus among prevention scientists and college administrators is that our interventions can continue to be strengthened (Hingson et al, 2005(Hingson et al, , 2009.…”
mentioning
confidence: 99%